2022
DOI: 10.3390/biomedicines10102633
|View full text |Cite
|
Sign up to set email alerts
|

Space Biomedicine: A Unique Opportunity to Rethink the Relationships between Physics and Biology

Abstract: Space biomedicine has provided significant technological breakthroughs by developing new medical devices, diagnostic tools, and health-supporting systems. Many of these products are currently in use onboard the International Space Station and have been successfully translated into clinical practice on Earth. However, biomedical research performed in space has disclosed exciting, new perspectives regarding the relationships between physics and medicine, thus fostering the rethinking of the theoretical basis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 102 publications
0
3
0
Order By: Relevance
“…We also did not discuss other potential applications of PPSS. Recent reviews on spaceflight, microgravity, and simulated microgravity have shown that multiple organ systems are involved in the response of the organism to these stressors [115][116][117][118][119][120]. The response to these stressors converges on the inflammatory response, which is a driver of aging [117].…”
Section: Limitationsmentioning
confidence: 99%
“…We also did not discuss other potential applications of PPSS. Recent reviews on spaceflight, microgravity, and simulated microgravity have shown that multiple organ systems are involved in the response of the organism to these stressors [115][116][117][118][119][120]. The response to these stressors converges on the inflammatory response, which is a driver of aging [117].…”
Section: Limitationsmentioning
confidence: 99%
“…A compelling body of evidence demonstrating how the cytoskeleton can capture and amplify even minor changes occurring in the field of force in numerous mammalian cells has emerged from biological research conducted in space and in microgravity (µg) conditions reproduced on Earth (modeled µg). Specific facilities, such as the monoaxial clinostats Rotating Wall Vessel (RWV) and Rotary Cell Culture System (RCCS), and the Random Positioning Machine (RPM) can be used to create µg in research laboratories [14][15][16][17]. The majority of research in this field has primarily focused on specific cell types, such as osteoblasts/osteoclasts [18][19][20], myofibers [21], endothelial cells [22][23][24], stem cells [25,26], fibroblasts [27][28][29][30][31] chondrocytes [32], lymphocytes [33] and other immune cells [34], with limited attention given to kidney cells [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Weightlessness is the state in which a body having a certain weight is balanced by another force or remains in free fall without feeling the effects of the atmosphere, equivalent to the situation faced by an astronaut aboard a spaceship. The effects of microgravity on human physiology have been studied extensively since the time of Yuri Gagarin (in 1961) who experienced the first man-on-board orbital flight, revealing profound implications for human health [2]. Despite the great interest and commitment of the scientific community, the mechanisms by which microgravity exerts its effects on the human body are not entirely clear.…”
Section: Introductionmentioning
confidence: 99%